The Influence of Industrial Work Practices on Employability Skills of Vocational High School - Nadia Salsabila Sifa; Sudjani Sudjani; Sri Rahayu (Jurnal Penelitian Pendidikan, 2022)
Industrial work practice is one of the efforts made by vocational high schools to produce graduates who have the appropriate skills which field is occupied through practice industrial work students can improve Employability Skills that can improve the quality of self in work. This is to find out the description of the work practice Industrial students of class XII DPIB SMK PU Negeri Bandung, know a description of the work ability of class XII students of DPIB vocational high school, and find out how much influence industrial work practices have on students' Employability Skills class XII DPIB vocational high school The research method used in this research is associative research with a quantitative approach. The population in this study were students of class XII DPIB which collected 69 students, with a research sample of 49 students. The data collection technique uses a questionnaire for both industrial work practices and Employability Skills the results of this study show a general. In general, the general description of the Employability Skills of the XII DPIB class XII students has a tendency of "High Enough", and there is influence Industrial Work Practices on Employability Skills of class XII DPIB students significantly.